A set-theoretic model reference adaptive control architecture with dead-zone effect. (August 2019) - Arabi, Ehsan; Yucelen, Tansel
Abstract: A new set-theoretic model reference adaptive control architecture with dead-zone effect is presented. The key feature of our approach utilizes a new generalized restricted potential function, where it not only provides a user-defined uncertain dynamical system performance but also has the capability to stop the adaptation when system errors are small (i.e., inside dead-zone ) — a practice adopted in adaptive control applications. The stability of the proposed technique is analyzed through showing the boundedness of an energy function in all possible variations and its experimental validation is also given through an aerospace testbed.